Readiness Survey And Comparison Of Educational Hospitals Of Medical Sciences University Of Urmia To Deploy Electronic Medical Records - Mostafa Langarizadeh; Elahe Gozali; Farahnaz Sadoughi (Tehran University of Medical Sciences, 2013)
Background and Aim: Development of information and communication technology has led to enormous changes in different areas. Electronic medical records system is valuable to access patient data in hospitals. This study aimed to investigate and compare the educational hospitals of Uemia University of Medical Sciences in case of technical, organizational and legal to establish the system. Materials and Methods: The study was a descriptive cross-sectional study. The study population consisted of 98 senior and central managers. In this study population census was used and the entire population were considered as the sample. A questionnaire was used for data collection, which included two sections in order to determine the level of research community awareness and to analyze the standards related requirements for the implementation of the system. Validity and reliability were assessed and the data was analyzed by SPSS. Results: Sample awareness in 5 hospitals of this study was moderate. In terms of requirements, there was a significant difference between the means of Electronic Medical Records in terms of three variables between hospitals "D" and the rest of the hospitals. And no significant difference was seen among other hospitals. Conclusion : Three hospitals, "a", "c" and "b", among five studied hospitals are in preparation for the deployment of electronic medical records. Other two hospitals were not prepared. However, the implementation of electronic medical records, increases health care quality, patient safety and patient care and also decreases health costs. So it is suggested that hospitals do necessary efforts to establish EMR.